2018
DOI: 10.3389/fphys.2018.00060
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training in Normobaric Hypoxia Leads to Greater Body Fat Loss in Overweight/Obese Women than High-Intensity Interval Training in Normoxia

Abstract: A moderate hypoxic stimulus is considered a promising therapeutic modality for several pathological states including obesity. There is scientific evidence suggesting that when hypoxia and physical activity are combined, they could provide benefits for the obese population. The aim of the present study was to investigate if exposure to hypoxia combined with two different protocols of high-intensity interval exercise in overweight/obese women was more effective compared with exercise in normoxia. Study participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 65 publications
2
46
0
Order By: Relevance
“…A greater decrease in total body weight, body fat mass and waist/hip ratio was found when exercise was performed under hypoxia compared to normoxia, and appeared to be maintained following the intervention . Interestingly, hypoxia exposure also seems to exert effects on substrate oxidation but findings are conflicting, with some studies showing increased fat oxidation, while others demonstrating increased carbohydrate oxidation both during and post‐exercise . Furthermore, exercise training under hypoxic conditions induced a more pronounced increase in adiponectin levels compared to normoxic exercise .…”
Section: Altered Tissue Oxygenation Impacts Whole‐body Physiology In mentioning
confidence: 99%
“…A greater decrease in total body weight, body fat mass and waist/hip ratio was found when exercise was performed under hypoxia compared to normoxia, and appeared to be maintained following the intervention . Interestingly, hypoxia exposure also seems to exert effects on substrate oxidation but findings are conflicting, with some studies showing increased fat oxidation, while others demonstrating increased carbohydrate oxidation both during and post‐exercise . Furthermore, exercise training under hypoxic conditions induced a more pronounced increase in adiponectin levels compared to normoxic exercise .…”
Section: Altered Tissue Oxygenation Impacts Whole‐body Physiology In mentioning
confidence: 99%
“…More recently, an emerging line of research has shown that, apart from the benefits of improving cardiorespiratory fitness in sedentary populations, hypoxic exercise seems to be a novel treatment strategy for weight loss and comorbidities in obese subjects [16,17,18,19,20]. However, hypoxia itself, may induce negative cognitive-related consequences as severity increases [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The HR and average training power during the training sessions were not significantly different between groups. Further detail on precise data can be found elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…13,39 Although there are insufficient studies on detraining effects available to discuss this question, there is a general consensus on performance at altitude being improved after around 10 days of exposure. 51 Therefore, significant decreases in fat mass parameters after 4 weeks of detraining in both hypoxia groups could reveal the role of normobaric hypoxia on lipid oxidation post-exposure 30,51 and its beneficial implications on body composition even after a detraining period. Similarly to HIIT, lipolytic pathways are the main drivers for the sympathetic nervous system through the release of catecholamines post-exposure.…”
Section: Discussionmentioning
confidence: 99%